468 Laterally extended parametrectomy (LEP). (13th November 2020) - Capilna, M; Kiss, SL; Cozlea, A; Stanca, M; Gheorghe, M
Abstract : Introduction: Laterally Extended Parametrectomy (LEP) was imagined by Ungar and Palfalvi as a more radical surgical procedure for the treatment of lymph node positive stage Ib and stage IIb cervical cancer. Methods: The aim of the technique is to remove the entire parametrial tissue containing lymphatic structures from the pelvic side wall. Results: LEP superposes to a type D Querleu-Morrow radical hysterectomy, extending the lateral limits of the dissection not only to the medial surface of hypogastric vessels, but to true borders of the pelvic side wall. Its rationale was to avoid the need of aggresive and deleterious postoperative radiotherapy for patients with positive pelvic lymph nodes or parametria in which the final histology suggested a complete removal of the potentially tumor containing lymph-vessel and lymph node containing fibro-fatty tissue. LEP may be also taken into consideration during pelvic exenteration, when the tumor involves the soft structures of the pelvic side wall, for a more extensive pelvic side wall dissection. During LEP, together with the visceral branches of hypogastric vessels, all the parietal branches are also divided (ilio-lumbal, obturator, gluteal superior and inferior and internal pudendal vessels) at the level where the vessels leave or enter into the pelvis. LEP can be performed on one or both pelvic sides, depending on parametrial invasion or presence positive lymph nodes uni- or bilaterally. Conclusion: LEP provides a good chance for survival without the toxicity of radiotherapy for pelvic lymph node positive stage Ib or IIb cervical cancer patients.